L27 Peripheral microencapsulated porcine sertoli cells for a xenograft neuroprotective treatment in huntington's disease. (13th September 2016) - Luca, Giovanni; Calafiore, Riccardo; Vescovi, Angelo; Squitieri, Ferdinando
Abstract : Background: Elongated Huntingtin (Htt) protein causes testes atrophy in models and a cascade of biological events in and out of the nervous system, including inflammation and production of factors such as cytokines. Recent evidence documented that testis-derived porcine Sertoli cells show neuroprotective properties. Objective: To investigate whether therapeutic approaches by peripheral transplantation of microencapsulated SCs may represent an effective strategy to counteract cell dysfunction within and out of the nervous system in HD. Methods: In order to prevent any transmission of infectious adventitious agents to the cells graft recipients, we have isolated porcine Sertoli (pSC) monolayers, obtained from specific pathogen free (SPF) certified neonatal pigs and born in the unique SPF colony. Cells were assessed for viability, by ethidium bromide and fluorescein diacetate (EB/FD), and characterised for Müllerian inhibiting substance (AMH), insulin-like 3 (INSL3), alpha-smooth muscle actin (ASMI), both by immunofluorescence (IF) and cytofluorimetric analysis (CA). pSC were encapsulated in alginate microcapsules (Ba-MCpSCs) and pSC functional competence was evaluated by AMH, inhibin B, TGF-β, IGF-I secretion. Results: We report the high purity of our pSC monolayers (95% of AMH+cells), with negligible contamination of Leydig (2%) and peritubular cells (3%). Microencapsulation did not alter pSC viability and even after 4 months post-implantation, has demonstrated that this treatment provide clear evidence of the neuroprotective and antiinflammatory effects by a single intraperitoneal injection in peritoneal cavity. Conclusions: The procedure we describe has the potential for human application in clinical practice. The beneficial effects of pSC monolayers, obtained from specific pathogen free (SPF) certified pSC transplantation in HD models, provide new perspectives for innovative, not particularly invasive, xenograft therapy in HD.